The EVALUATION AND PLANNING IN CONTRACTS AGROBUSINESS AS STRATEGIES OF UNCERTAINTY minimizing transaction costs - Francisco JosÃ Mendes Vasconcelos (2014)
The present study aimed to analyze the applicability of legal theories ImprevisÃo and avoidable damage in minimizing the effects of uncertainty in the agribusiness contracts. To examine such application, first, secondary data extracted from time series database of IBGE and IPEA-DATA in the estimation of an econometric model, where methods of time series, unit root test, test were employed were worked co-integration Johansen model vector error correction and variance decomposition of forecast errors. This econometric procedure aims to demonstrate margins of errors in the prognosis of future data. The sample period covers January 2007 to December 2011. As an additional function was taken concomitantly, a research field whose basic aim was to characterize the contractual relationship of an agribusiness production chain. The supply chain was chosen the culture of cashew in the state of CearÃ. The set of results in a systemic way, demonstrates that despite all the caring of economic agents in running a successful strategic planning within their productive activity, there is always a "gray area", under the impenetrable human perspective, imbued with extraordinary facts and unpredictable that when they occur, cause imbalance in contracts. This means that the fatality not envisioned by econometric methods, the legal instruments supplementing them in order to adjust the contracts, rebalancing them again.